Designer's guide to Eurocode 9 design of aluminium structures : EN 1999-1-1 and -1-4 - Hoglund, Torsten (ICE, 2012)
Detailing the requirements for resistance, serviceability, durability & fire resistance in the design of buildings & other civil engineering & structural works in aluminium, this guide provides the user with guidance on the interpretation of standards contained in EN 1999.